Pilot Testing a Robot for Reducing Pain in Hospitalized Preterm Infants. (April 2019) - Williams, Nicholas; MacLean, Karon; Guan, Ling; Collet, Jean Paul; Holsti, Liisa
Optimizing neurodevelopment is a key goal of neonatal occupational therapy. In preterm infants, repeated procedural pain is associated with adverse effects on neurodevelopment long term. Calmer is a robot designed to reduce infant pain. The objective of this study was to examine the effects of Calmer on heart rate variability (HRV) during routine blood collection in preterm infants. In a randomized controlled pilot trial, 10 infants were assigned to either standard care ( n = 5, facilitated tucking [FT]) or Calmer treatment ( n = 5). HRV was recorded continuously and quantified using the area (power) of the spectrum in high and low frequency (HF: 0.15-0.40Hz/ms 2 ; LF: 0.04-0.15 Hz/ms 2 ) regions. Changes in HRV during three, 2-min phases (Baseline, Heel Poke, and Recovery) were compared between groups. Calmer infants had 90% greater parasympathetic activation ([PS] reduced stress) during Baseline, 82% greater PS activation during Poke, and 24% greater PS activation during Recovery than FT infants. Calmer reduced physiological preterm infant pain reactivity during blood collection.